Penataan Organisasi KPSDMP-KP di Kabupaten Garut, Provinsi Jawa Barat - Faria Ruhana (Universitas Riau, 2009)
The agricultural sector in Indonesia is very important in the national economy. Therole of government, private sector and farmers must work together to ensure the sustainabilityof agricultural development. Agriculture counseling organization as technical provider shouldbe ready to bridge the communication between the private sector, farmers and thegovernment itself. Although the improvements have been made several times, however in thefact shows that agriculture counseling organizations have not been working properly.This research with method of survey was conducted to know organization arrangement in theKantor Pengembangan Sumber Daya Manusia Pertanian dan Ketahanan Pangan (KPSDMP-KP) Garut Regency, review of the Hellriegel and Slocum theory (1998;581), development ofthe theory related to the issues in the research area, and alternative model of organizationstructure KPSDMP KP based findings on the problem formulation.Result of research indicate that human resources and technology get the lowest ratings of therespondents so that changes and improvements should start from both dimension. In addition,obtained by special finding that availability of information technology is very important insettlement of organization. The development of organization structure model of the KPSDMPKP Garut Regency is required two additional sections, that is 1) Study and Development ofAgriculture Technology and 2) Information Technology Section.